Governance of the Handover of Infrastructure, Facilities, and Public Utilities in Housing Areas in Balikpapan City - Arief Bandoro Sigit; Bambang Irawan; Cathas Teguh Prakoso (Universitas Pancasakti, 2026)
This study examines the governance of the handover of infrastructure, facilities, and public utilities in housing areas in Balikpapan City by focusing on regulatory compliance, institutional coordination, administrative mechanisms, and stakeholder participation. Using a qualitative descriptive approach supported by in-depth interviews, document analysis, and field observations involving local government officials, developers, community representatives, and related institutions, this research analyzes the implementation of handover policies and identifies major challenges affecting their effectiveness. The findings indicate that although regulatory frameworks are well established, their implementation remains inconsistent due to weak institutional coordination, incomplete administrative documentation, limited verification mechanisms, variations in developer compliance, and low levels of community participation. These conditions reflect gaps between policy objectives and operational practices, which are influenced by limited institutional capacity and fragmented communication among stakeholders. The study further reveals that effective governance in the handover process requires strong collaboration, integrated administrative systems, continuous supervision, and greater transparency. Strengthening document management, enhancing human resource capacity, and expanding participatory mechanisms are essential to improve accountability and sustainability. This research contributes to the understanding of housing governance by highlighting the interdependence of regulatory, administrative, and social dimensions in public infrastructure management and provides practical insights for policymakers in developing more transparent, accountable, and sustainable governance frameworks for housing development and public service delivery.